The Implementation and Historical Perspective of Health Law in Law No. 17 of 2023 - Yandi, Rus; Zuhri, Basrial; Yatim, Yenita; Kaksim, Kaksim (The Future of Education Journal, 2025)
The Indonesian Health Law has experienced a tug-of-war of interests between the government, the medical profession, and the community. Historically, it has experienced a few problems. Initially, the government tended to emphasize aspects of efficiency and regulatory control, but the medical profession highlighted the issues of professionalism and autonomy, and the community emphasized health rights and public participation. The purpose of the study was to trace the dynamics of initiation, the substance of the omnibus law with changes in the fundamentalism of health law, issues of overlapping regulations, reduced role of professional organizations, low socialization in the community. The literature review research method combines a normative legal approach and empirical analysis based on journal articles, proceedings, and other sources. The study uses secondary data, namely scientific articles. The primary is the text of the law. The results of the first study, the responsibility of the hospital can be held civilly accountable. Second, the mechanism for medical disputes in law enforcement is not yet consistent, lack of socialization of medical personnel and patients, the need for integration of mediation technology and legal education. Three, technical challenges arise, low digital literacy, data leakage, limitations of remote diagnosis. Four, regulations for people with disabilities. five, the process of derivative regulations and socialization of legal materials must be followed up through PP, Perpres, Permenkes with careful planning. six, Attention to victims of sexual violence. In conclusion, an omnibus was born that integrated 11 previous health laws. but there are still findings of problems with mimin socialization, law enforcement and the capacity of health workers.